Analysis of Collaborative Learning Implementation for Achieving Learning Outcomes Based on Mastery Standards in Islamic Education Subject - Alauddin Alauddin; St. Marwiyah; Indah Lestari; Nurul Aswar (South Sulawesi Education Development (SSED), 2023)
This study aims to determine whether applying Collaborative Learning in Islamic Religious Education Subjects can achieve the learning outcomes of grade VIII students of Datok Sulaiman Junior High School Palopo Girls. The data sources used are primary data and secondary data. This type of research is descriptive qualitative, with data collection techniques, namely interviews, observation and documentation. The number of informants used in this study was 37 respondents. The results showed that the application of collaborative learning began with the teacher giving greetings, praying, dividing groups and materials, students conducting discussions and presentations in front of the class and, at the end of learning, doing quizzes as a form of evaluation. The application of collaborative learning provides ease in understanding learning more active, pleasant atmosphere. Obstacles in implementing cooperative learning include lack of cooperation, delivery of material in a small voice, relatively short processing time, limited internet access and differences of opinion. Learning outcomes through collaborative learning provide very satisfactory learning outcomes with a pass rate of 100% above KKM.